1991
DOI: 10.1152/ajprenal.1991.261.6.f982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibitors of oxidative phosphorylation on erythropoietin mRNA in isolated perfused rat kidneys

Abstract: We have used RNase protection to measure oxygen-dependent changes in erythropoietin (EPO) mRNA in isolated perfused kidneys and to compare the effect of hypoxia with the response to inhibitors of oxidative phosphorylation. In well-oxygenated kidneys perfused for 2 h at 12 ml/min, with hematocrit of 0.09 +/- 0.005 and PO2 of 443 +/- 67 mmHg, EPO mRNA levels were similar to the baseline levels measured in nonperfused contralateral kidneys from the same animals. When perfusions were performed under identical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…4A). In contrast, but in keeping with the physiological regulation of the Epo gene (14,15), hypoxic stimulation in a23 cells was not mimicked by exposure to cyanide. Thus, cyanide (10-1000 ,uM) did not induce enhancer activity, nor did it abrogate the response to concurrent hypoxic stimulation (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…4A). In contrast, but in keeping with the physiological regulation of the Epo gene (14,15), hypoxic stimulation in a23 cells was not mimicked by exposure to cyanide. Thus, cyanide (10-1000 ,uM) did not induce enhancer activity, nor did it abrogate the response to concurrent hypoxic stimulation (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Thus, it is activated by cobalt, but not by cyanide, and is abrogated by cycloheximide (5,6,(13)(14)(15). The dose range of cyanide was chosen to include concentrations which cause minimal, partial, and total inhibition of cellular respiration (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…Special attention was given to the differences in sensitivity to hypoxia and cyanide or antimycin of intracellular haem proteins, since it has been reported that Epo production can be stimulated by hypoxia but not by cyanide poisoning (Goldberg et al, 1988) or by other inhibitors of the respiratory chain (Tan and Ratcliffe, 1991). We postulate, therefore, that the putative haem protein responsible for the oxygen-sensing process in HepG2 cells should be sensitive to hypoxia only.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms including NADPH oxidase (9), cytochrome P 450 (10), and an O 2 -binding heme protein (11) have been proposed. Mitochondria have been considered as possible O 2 sensors, but mitochondrial inhibitors failed to activate transcription (12). But recent work has implicated mitochondria in the O 2 sensing underlying functional responses to hypoxia (13).…”
mentioning
confidence: 99%